The Effect of TikTok Exposure on Attitudes, Subjective Norms, and Intentions to Promote Pro-Environmental Behavior among Universitas Padjadjaran Students - Arjani, Naura; Kunto Adi Wibowo; Detta Rahmawan; Ikhsan Fuady (UM Purwokerto Press, 2025)
Climate change necessitates behavioral transformation among Generation Z, who are heavily influenced by TikTok. This study analyzes the impact of TikTok exposure on pro-environmental behavior among Universitas Padjadjaran students using the Theory of Planned Behavior. Data from 310 respondents were processed using SEM-PLS. Results indicate that TikTok exposure significantly is significantly associated with attitudes and subjective norms, driving environmental intentions and actions. A critical finding reveals that attitude (T-Stat 10.761) serves as a stronger mediator than subjective norms (T-Stat 6.943), suggesting that personal conviction outweighs social pressure. The model shows strong predictive power, with behavioral intention demonstrating a strong association with pro-environmental behavior (T-Stat 101.724). In conclusion, TikTok effectively mobilizes environmental action by internalizing personal values rather than mere social conformity.